Efektivitas Dinas Sosial Pemuda dan Olahraga dalam Penanganan Anak Jalanan di Kota Semarang - Maharani, Aprillia; Yuniningsih, Tri; Djumiarti, Titik (Journal of Public Policy and Management Review, 2016)
This study attempts to analyze and describe the effectiveness of Social Services of Youth and Sports in the handling of street children in the City of Semarang. This research uses qualitative approach with descriptive method. The focus of this study include productivity, adaptation, motivation and the factors that influence the effectiveness of Social Services of Youth and Sports in the managing of street children. The results show that Social Service of Youth and Sports of Semarang City has quite effective in terms of fulfilling the basic needs which is shelter to protect the street children from harmful things, clothing for the street children including uniform, daily wear, also nutrition for the street children in form of food support. Advice that provided is the effectiveness of managing the street children needs to be improved by improving the equalization of services for the street children, improving the ability of the employee, and improving the socialization for the community about the managing of street children.